META ANALISIS EFEKTIFITAS PROBLEM BASED LEARNING DAN PROBLEM SOLVING DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Yulia Yulia; Mawardi Mawardi (Universitas Negeri Medan, 2021)
Abstract: Meta Analysis of the Effectivenecc of Problem Based Learning and Problem Solving in terms of Critical Thinking Ability of Elementary School Students. In quantitative research, Meta Analysis aims to determine whether the Problem Based Learning and Problem Solving learning model has a high influence on improving critical thingking skills in elementary school students. the techniquenused used is the Effect Size technique analysis with the Effect Size formula. The instrument used was a worksheet instrument for coding the result of scientific publications that were searched through the internrt. The variables studied to obtain information about the magnitude of the effect of thus Effect Size are the Problem Based Learning and Problem Solving learning models as independent variables, and critical thingking skills as the dependent variable. From the results of the research the has been done, it shows that the measurement results of critical thingking skills in learning using the Problem Solving learning model are significantly higher than Problem Based Learning, meaning that the Problem Solving learning model is more effective in increasing the critical thingking skills of elementary school student. Judging from the Ancova test, the average value of Experiment 2 in the Problem Solving learning model is 83.3000 higher than the Problem Based Learning model of 76.0420. based on the results of the calculation of the hypothesis test using the Ancova test using Univariate which shows that the significance value is 0,009, which means less than 0,05 (0,009 < 0,05). From the Ancova test, it shows that F count > F table is 11,311 with a significance of 0,009 < 0,05, which indicates that Ho is rejected and Ha is accepted. From the resultas of this test, it shows that the Effect Size of the Problem Solving learning model is significantly larger that the Problem Based Learning in terms of the critical thingking abilities of elementary school students. Keywords: Meta Analysis, Problem Based Learning, Problem Solving, Critical Thingking Skills. Abstrak: Meta Analisis Efektifitas Problem Based Learning Dan Problem Solving Ditinjau Dari Kemampuan Berpikir Kritis Siswa Sekolah Dasar. Dalam penelitian kuantitatif Meta Analisis bertujuan untuk mengetahui apakah model pembelajaran Problem Based Learning dan Problem Solving memiliki pengaruh yang tinggi terhadap peningkatan keterampilan berpikir kritis pada siswa sekolah dasar. Teknik yang digunakan adalah analisis teknik Effect Size dengan rumus Effect Size. Instrument yang digunakan yaitu instrument lembar kerja pemberian koding terhadap hasil publikasi ilmiah yang ditelusuri melalui internet. Variabel yang diteliti untuk memperoleh informasi mengenai besar pengaruh Effect Size ini adalah model pembelajaran Problem Based Learning dan Problem Solving sebagai variabel bebas, serta keterampilan berpikir kritis sebagai variabel terikat. Dari hasil penelitian yang telah dilakukan menunjukan bahwa hasil pengukuran keterampilan berpikir kritis dalam pembelajaran menggunakan model pembelajaran Problem Solving lebih tinggi secara signifikan dibandingkan dengan Problem Based Learning, artinya model pembelajaran Problem Solving lebih efektif terhadap peningkatan keterampilan berpikir kritis siswa sekolah dasar. Dilihat dari uji Ancova, nilai rata-rata Eksperimen 2 model pembelajaran Problem Solving sebesar 83,3000 lebih tinggi dibandingkan dengan model pembelajaran Problem Based Learning sebesar 76,0420. Berdasarkan hasil perhitungan uji hipotesis dengan menggunakan uji Ancova menggunakan Univariate yang menunjukan bahwa nilai signifikansi sebesar 0,009 yang berarti lebih kecil dari 0,05 (0,009 < 0,05). Dari uji Ancova menunjukan F hitung > F tabel yaitu 11,311 dengan signifikansi 0,009 < 0,05 yang menunjukan bahwa Ho ditolak dan Ha diterima. Dari hasil uji ini menunjukan bahwa Effect Size model pembelajaran Problem Solving lebih besar secara signifikan dibandingkan dengan Problem Based Learning ditinjau dari kemampuan berpikir kritis siswa sekolah dasar. Kata Kunci: Meta Analisis, Problem Based Learning, Problem Solving, Keterampilan Berpikir Kritis.